1995
DOI: 10.1152/ajpendo.1995.268.4.e668
|View full text |Cite
|
Sign up to set email alerts
|

Long-term adaptive responses to dietary protein restriction in chronic renal failure

Abstract: Six patients with chronic renal failure (glomerular filtration rate 18 +/- 2 ml/min) underwent two 10-day admissions separated by at least 1 yr of outpatient therapy with a very low-protein diet (VLPD) providing 0.28 g protein.kg-1.day-1 plus an amino acid-ketoacid supplement. During each Clinical Research Center admission, subjects completed a 5-day nitrogen balance (BN), and whole body protein turnover was measured during fasting and feeding using intravenous [1-13C]leucine and intragastric [5,5,5-2H3]leucin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
63
0
1

Year Published

1997
1997
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(66 citation statements)
references
References 3 publications
2
63
0
1
Order By: Relevance
“…Our results are in accordance with previous studies using VLPD þ KA for longer periods of time (Mitch et al, 1982;Walser, 1993;Masud et al, 1994;Tom et al, 1995). Indeed, isotopic studies that evaluated protein metabolism showed that for both shortterm and long-term treatment periods, neutral or positive nitrogen balance is attained in patients receiving a VLPD þ KA, yet energy intake was below the recommended 146 kJ/kg/day (35 kcal/kg/day) (Masud et al, 1994;Tom et al, 1995). Similar results regarding low energy intake and maintenance of nutritional parameters were also observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in accordance with previous studies using VLPD þ KA for longer periods of time (Mitch et al, 1982;Walser, 1993;Masud et al, 1994;Tom et al, 1995). Indeed, isotopic studies that evaluated protein metabolism showed that for both shortterm and long-term treatment periods, neutral or positive nitrogen balance is attained in patients receiving a VLPD þ KA, yet energy intake was below the recommended 146 kJ/kg/day (35 kcal/kg/day) (Masud et al, 1994;Tom et al, 1995). Similar results regarding low energy intake and maintenance of nutritional parameters were also observed in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Although concern has been raised about the nutritional adequacy of these diets and the risk for the subsequent development of malnutrition (Aparicio et al, 2001) studies have demonstrated that a VLPD þ KA in carefully selected and motivated patients with advanced CKD has no deleterious influence on some nutritional parameters in the predialysis phase of CKD (Mitch et al, 1982;Walser, 1993;Masud et al, 1994;Tom et al, 1995;Aparicio et al, 2001). However, only a few studies have included a control group and patients that were previously following a conventional low protein diet.…”
Section: Introductionmentioning
confidence: 99%
“…This is not surpris- ing since a HPD is known to stimulate leucine oxidation (12,19) and would obscure the influence of proteinuria.…”
Section: Resultsmentioning
confidence: 99%
“…The contribution of the formula meal to background 13 CO 2 enrichment was determined on day 9 by collecting expired breath samples during feeding using an identical protocol to that described for the whole-body leucine turnover, except that tracers were not infused (10,19). To minimize its contribution to background 13 CO 2 enrichment, foods with a low 13 C abundance were chosen for the formula meal (20).…”
Section: Tracer Infusion Studies (A) Sham Infusionmentioning
confidence: 99%
See 1 more Smart Citation